The Role of the Makassar City Trade Office in Empowering UMKM During the Covid 19 Period - Gilang Ramadhan (Income Journal Of Economics Development, 2023)
The purpose of this research is a type of qualitative research. With the aim of knowing The implementation of the BLT program in Bissappu District is a program created to meet the needs of residents during the Covid-19 pandemic. The mechanism for collecting data on the BLT program in Bissappu District includes: data collection, determination of BLT recipients, consolidation and verification of recipients, validation and determination of data collection results, and the last is the distribution of aid. So that the existence of the BLT-Dana Desa program in Bissappu District can at least increase the consumption of families receiving the BLT-Dana Desa, ensure the maintenance of social welfare levels, and maintain financial stability. supporting factors consist of aspects: quality of program policies, capacity of implementers, budget adequacy, and characteristics of the target group. While the inhibiting factors include the inhibiting factor is the dishonest character and characteristics of unscrupulous village officials as policy implementers. The results of this study indicate that the policies carried out by the government have an impact on the implementation of the BLT-Village Fund policy to the poor affected by Covid-19 in Bissappu District in the form of a positive impact, namely the expected impact where the assistance is properly utilized to ease the burden of life for poor families as a source of income. impact of the Covid-19 pandemic. While the negative impact is an unexpected impact where with the provision of such assistance by the government, the community becomes spoiled and always waits for assistance from the government, Also the assistance is used for things other than their basic needs.